Tatalaksana Gangguan Spektrum Autisme pada Anak: Tinjauan Cakupan - Syahrir, Akifa; Hartini, Sri (Journal of Islamic Nursing, 2024)
Autism spectrum disorder (ASD) is estimated to affect 1 in 59 children and this number continues to increase each year. Children with ASD have the same basic healthcare needs as children without disabilities and benefit from the same health promotion and disease prevention activities. The purpose of this study was to identify research interventions for children with ASD in various healthcare settings. This literature search used the PCC (Population, Content, and Context) method with Boolean conjunctions “AND” and “OR”. The databases used in this literature search were EBSCO, Clinical Key Nursing, and PubMed with a search strategy using the keywords Pediatric OR Child AND Autism Spectrum Disorder OR Autism AND Management OR Intervention OR Treatment OR Guideline. Articles included in the review results included articles with a publication year range of 2009-2019, original articles, and research involving the concept of ASD in children. From the search results of various databases, 8 articles of the latest findings were obtained with the implementation of interventions in minimizing disorders that occur in children with ASD with 5 Randomized Control Trial article designs, 2 articles with quasi-experimental, and 1 qualitative article. The results of this literature were then managed into 2 major themes that became components of the discussion of this writing, namely behavioral development, social interaction, and communication. Nurses are considered responsible for following up on various medical care plans that can be very difficult with children with autism. The most important role of a nurse in autism is essentially providing education to parents/caregivers to meet the needs of children with ASD.